Stakeholder Collaboration Model for Ecotourism Development in Indonesia: Case Study from Batu City East Java Province - I Gede Eko Putra Sri Sentanu; Ardian Prabowo; Klara Kumalasari; Aulia Puspaning Galih; Rendra Eko Wismanu (Universitas Muhammadiyah Tangerang, 2021)
This research aims at creating a concept of cooperation between stakeholders in developing eco-tourism in Batu City. Eco-tourism and the role of stakeholders are related to one another. It is due to the urge of stakeholders to work together in managing the potential of eco-tourism to achieve a development goal. This study applies the Penta-helix model and triple-bottom-line theories to investigate the contribution of stakeholders to sustainable development. The Penta-helix model is used to identify relevant stakeholders and conduct effective collaboration. At the same time, the triple-bottom-line is applied to observe the environmental and socio-economic aspects of the eco-tourism sector. This study employs a qualitative method with an interactive approach from Miles, Huberman, and Saldana by deepening literary understanding; and field interviews. The results of this study show that cooperation and interaction between stakeholders in developing eco-tourism are inferior. Thus, the researchers develop a stakeholder collaboration model through the Penta-helix model covering the government, private eco-tourism enterprises, communities, academics, and the media. They collaborate in determining the sustainability agendas covering environmental, economic, and social as a reflection of the triple bottom line element. Those designed agendas are to encourage the realization of eco-tourism development in Batu City, Indonesia. The research recommends further research to evaluate whether this eco-tourism development model can be effective if implemented. Penelitian ini bertujuan untuk menciptakan konsep kerjasama antar stakeholder dalam pengembangan ekowisata di Kota Batu. Karena ekowisata dan peran pemangku kepentingan berkaitan satu sama lain. Hal ini dikarenakan adanya dorongan dari para pemangku kepentingan untuk bekerja sama dalam mengelola potensi ekowisata untuk mencapai tujuan pembangunan. Studi ini menerapkan model penta helix dan teori triple bottom line untuk menyelidiki kontribusi pemangku kepentingan terhadap pembangunan berkelanjutan. Model Penta helix digunakan untuk mengidentifikasi pemangku kepentingan yang relevan dan untuk melakukan kolaborasi yang efektif, sedangkan triple bottom line diterapkan untuk mengamati aspek lingkungan dan sosial ekonomi dari sektor ekowisata. Penelitian ini menggunakan metode kualitatif dengan pendekatan interaktif dari Miles, Huberman, dan Saldana dengan pendalaman pemahaman literatur; dan wawancara lapangan. Hasil penelitian ini menunjukkan bahwa kerjasama dan interaksi antar pemangku kepentingan dalam pengembangan ekowisata masih rendah. Oleh karena itu, peneliti mengembangkan model kolaborasi pemangku kepentingan melalui model Penta helix yang mencakup pemerintah, swasta, komunitas, akademisi, dan media. Mereka berkolaborasi dalam menentukan agenda keberlanjutan yang meliputi lingkungan, ekonomi, dan sosial sebagai cerminan dari elemen triple bottom line. Agenda yang dirancang tersebut adalah untuk mendorong terwujudnya pembangunan ekowisata di Kota Batu, Indonesia. Peneliti merekomendasi pada penelitian selanjutnya untuk mengevaluasi apakah model pembangunan ekowisata ini dapat efektif jika diimplemetasikan.